The Role of MSMEs, Infrastructure and Cooperatives on DKI Jakarta Economic Growth - Johan, Ria Susanti; Hubeis, Musa; Karno (Future Science / FSH-PH Publications, 2022)
MSMEs, infrastructure and cooperatives were the determining factors for economic growth. Good and stable economic growth would have an impact on people's welfare. Economic growth was a process not an economic picture at a dynamic time of an economy. This study aimedd to describe the influence of MSMEs on economic growth, describe the influence of infrastructure on economic growth, describe the effect of cooperatives on economic growth and described MSMEs, Infrastructure and cooperatives on the economic growth of DKI Jakarta. The method used is a quantitative method. The data was taken from the national statistical center for the period 2015, 2016, 2017, 2018 and 2019. The data was processed using SPSS 21. Prerequisite tests include normality test, homoenity test and heteroscedasticity test. Hypothesis testing includes t test, F test and coefficient of determination. The results showed that MSMEs had an effect on economic growth, Infrastructure had an effect on economic growth, cooperatives had an effect on economic growth and MSMEs, infrastructure, cooperatives had a simultaneous effect on economic growth in DKI.The implication of the result was Expansion of job opportunities and employment. Formation of Gross Domestic Product (GDP). Provision of safety nets, especially for low-income people to carry out productive economic activities.